Infected Radicular Cyst. Review of Basic Concepts and A Clinical Case Report - Rojas Jimenez DDS, Diego; Zamora Arce, Daniela; Vargas Monge, Natalia; Guillén Colombari DDS, MSc, Diego (Odovtos - International Journal of Dental Sciences, 2015)
Odontogenic cysts are divided into development and inflammatory cysts. Periapical or radicular cyst of inflammatory origin, remains the most frequently described odontogenic cyst and is formed from the epithelial rests of Malassez in the periodontal ligament as a result of apical periodontitis after the pulpal necrosis. The treatment of these lesions is variable, sometimes the lesion is resolved with an endodontic treatment, or combination with certain surgical procedures (biopsy, marsupialization, decompression). However, in cases do not resolved with the initial endodontic treatment or retreatment, which should be combined with enucleation, apicoectomy. It is presented bellow a clinical case of a male patient with a tumor lesion on the vestibular sulcus in oral mucosa associated with dental organ 1.1. Radiological study was performed, it proceeds with incisional biopsy resulting reports periapical cyst, surgically enucleation and curettage of the lesion was performed.